The relationship between the pathological course of the gestation period and the experienced acute respiratory infection at different terms of pregnancy [Stockholm] - Sokolovska, I. S.; Ganzhiy, I. Yu.; Соколовська, Ірина Сергіївна; Ганжий, Ірина Юріївна (Stockholm : International Center of Scientific Research, 2023)
Annotation. The most typical gestational complications after acute respiratory infections are: placental dysfunction (22.4%), fetal growth retardation syndrome (9.9%), intrauterine infections (22.4%), congenital malformations of the fetus (7.8%). An increase in the frequency of placental dysfunction by more than 2 times in the early stages significantly increases the likelihood of developing fetal growth retardation syndrome by 1.8 times. The risk of fetal pathology increases 3.1 times with an acute respiratory infection suffered in the 1st trimester, 1.5 times with an acute respiratory infection in the 2nd trimester and 2.6 times with an acute respiratory infection in the 3rd trimester of gestation. The time interval between an episode of acute respiratory infection and the manifestation of placental dysfunction is 8.64±1.13 weeks.